Women's Beliefs on Early Adherence to Adjuvant Endocrine Therapy for Breast Cancer: A Theory-Based Qualitative Study to Guide the Development of Community Pharmacist Interventions - Brittany Humphries; Stéphanie Collins; Laurence Guillaumie; Julie Lemieux; Anne Dionne; Louise Provencher; Jocelyne Moisan; Sophie Lauzier (MDPI AG, 2018)
Adjuvant endocrine therapy (AET) taken for a minimum of five years reduces the recurrence and mortality risks among women with hormone-sensitive breast cancer. However, adherence to AET is suboptimal. To guide the development of theory-based interventions to enhance AET adherence, we conducted a study to explore beliefs regarding early adherence to AET. This qualitative study was guided by the Theory of Planned Behavior (TPB). We conducted focus groups and individual interviews among women prescribed AET in the last two years (n = 43). The topic guide explored attitudinal (perceived advantages and disadvantages), normative (perception of approval or disapproval), and control beliefs (barriers and facilitating factors) towards adhering to AET. Thematic analysis was conducted. Most women had a positive attitude towards AET regardless of their medication-taking behavior. The principal perceived advantage was protection against a recurrence while the principal inconvenience was side effects. Almost everyone approved of the woman taking her medication. The women mentioned facilitating factors to encourage medication-taking behaviors and cope with side effects. For adherent women, having trouble establishing a routine was their main barrier to taking medication. For non-adherent women, it was side effects affecting their quality of life. These findings could inform the development of community pharmacy-based adherence interventions.